Anti-tick effect and chemical composition of the molasses grass essential oil - Prates, Hélio T.; Oliveira, Alaíde B.; Leite, Romário C.; Craveiro, Afrânio A. (Pesquisa Agropecuaria Brasileira, 1993)
The essential oil of molasses grass (Melinis minutiflora Beauv.) obtained by steam distillation and the monoterpenes a and b-pinene have been tested against Boophilus microplus larvae showing lethal effect within ten minutes. GC/MS analysis of the molasses grass essential oil allowed the identification of four out of the five major constituents as hexanal, 1,8-cineole, 2,6-di-t-butil-4-methylphenol and 9-(E)-eicosene. The 2,6-di-t-butil-4-methylphenol was found in the diethyl ether used for the extraction of the essential oil.